Leukemia Inhibitory Factor Represses GnRH Gene Expression via cFOS during Inflammation in Male Mice - Lainez, Nancy M. (Neuroendocrinology, 2019)
BACKGROUND: The mechanisms whereby neuroinflammation negatively affects neuronal function in the hypothalamus are not clear. Our previous study determined that obesity-mediated chronic inflammation elicits sex-specific impairment in reproductive function via reduction in spine density in gonadotropin-releasing hormone (GnRH) neurons. Neuroinflammation and subsequent decrease in GnRH neuron spine density was specific for male mice, while protection in females was independent of ovarian estrogens. METHODS: To examine if neuroinflammation-induced cytokines can directly regulate GnRH gene expression, herein we examined signaling pathways and mechanisms in males in vivo and in GnRH-expressing cell line, GT1–7. RESULTS: GnRH neurons express cytokine receptors, and chronic or acute neuroinflammation represses GnRH gene expression in vivo. Leukemia inhibitory factor (LIF) in particular represses GnRH expression in GT1–7 cells, while other cytokines do not. STAT3 and MAPK pathways are activated following LIF treatment, but only MAPK pathway, specifically p38α, is sufficient to repress the GnRH gene. LIF induces cFOS that represses the GnRH gene via the −1,793 site in the enhancer region. In vivo, following high-fat diet, cFOS is induced in GnRH neurons and neurons juxtaposed to the leaky blood brain barrier of the organum vasculosum of the lamina terminalis, but not in the neurons further away. CONCLUSION: Our results indicate that the increase in LIF due to neuroinflammation induces cFOS and represses the GnRH gene. Therefore, in addition to synaptic changes in GnRH neurons, neuroinflammatory cytokines directly regulate gene expression and reproductive function, and the specificity for neuronal targets may stem from the proximity to the fenestrated capillaries.